KAJIAN BIAYA PEMUPUKAN TANAMAN MENGHASILKAN KELAPA SAWIT (Elaeis guineensis Jacq) DI DIVISI F KEBUN SEI KALAM PT. ASAM JAWA - Tuty Ningsih; Dimas Akbar Ramadhan Lubis; Saroha Manurung (Institut Teknologi Sawit Indonesia, 2019)
Fertilization in oil palm plants plays a very important role, more than 50% of the cost of the plant is used for fertilization. The hybrid oil palm currently being developed is generally very responsive to fertilization. Fertilization is a very important factor to increase the productivity and quality of the production produced. Fertilization is useful to provide nutrients needed by plants in order to carry out physiological processes that produce good growth and production. Fertilization costs are relatively high, approximately 30% of the total production costs or 40-60% of the total maintenance costs. The costs required to carry out fertilization activities are very large so that proper fertilization planning is needed to be effective and efficient. In productive plants can be done effectively 4T fertilization techniques, namely the right type, right dose, right on target, and on time. Based on this, observations were made on the study of fertilizer costs on plantations. This research was conducted in Division F of Sei Kalam Gardens, PT. Asam Jawa, Labuhanbatu Selatan Regency, North Sumatra Province. The time for the research to begin in March 2019 until May 2019.